1986
DOI: 10.1016/0014-5793(86)80892-4
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation of ornithine decarboxylase by polyamines

Abstract: The activity of ornithine decarboxylase (ODC), the first and rate-limiting enzyme in the polyamine biosynthetic pathway, is dramatically increased in proliferating cells. In addition to transcriptional regulation of ODC, the present study shows that the enzyme is regulated at the translational level by putrescine and spermidine. ODC synthesis is inhibited by an increase and stimulated by a decrease in their cellular content. Spermidine is a more potent negative regulator than is putrescine. The effects of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 19 publications
2
54
0
1
Order By: Relevance
“…It has also been reported that, directly adding large concentrations of putrescine to tissue culture systems, does not affect the levels of the induced ornithine decarboxylase mRNA (Holtta and Pohjanpelto, 1986;Persson, Holm and Heby, 1986). Polyamines may exert a negative feedback inhibition of the rate of translation of the ornithine decarboxylase mRNA.…”
Section: Inducedmentioning
confidence: 99%
“…It has also been reported that, directly adding large concentrations of putrescine to tissue culture systems, does not affect the levels of the induced ornithine decarboxylase mRNA (Holtta and Pohjanpelto, 1986;Persson, Holm and Heby, 1986). Polyamines may exert a negative feedback inhibition of the rate of translation of the ornithine decarboxylase mRNA.…”
Section: Inducedmentioning
confidence: 99%
“…The extract was then centrifuged for 20 rain at 20,000 x g at 4°C. SSAT, S-adenosylmethionine decarboxylase and ornithine decarboxylase activities were determined in aliqaots of the supernatant essentially as described earlier [20,21].…”
Section: Determination Of Enzyme Activitiesmentioning
confidence: 99%
“…To ascertain that the feedback control of ODC was effective in the non-transfected COS cells, ODC activity was measured in cells grown in the presence or absence of 10 pM spermidine. This concentration of spermidine is high enough to inhibit the synthesis of ODC in other mammalian cells [16,17, 191. A marked increase in ODC activity was observed in COS cells during their exponential growth (Fig.…”
mentioning
confidence: 99%
“…However, to obtain this effect large quantities of polyamines, often at millimolar concentrations, have to be used. Nevertheless, ODC is downregulated by the addition of micromolar concentrations of polyamines to cells [14,16,17, 191. Furthermore, treatment with polyamine synthesis inhibitors causes a marked increase in cellular ODC content which cannot be explained by a change in the apparent turnover of the enzyme [13,14, 191.…”
mentioning
confidence: 99%
See 1 more Smart Citation